Organizational prerequisites of graphic reform of the national language in Turkish Republic (Journal of Oriental Studies, 2017)
This article examines the factors that have affected the process of latinization of the Turkish language, namely the experience of Azerbaijan in the transition to the Latin alphabet. At the same time, the issue of transition to Latin was in Turkey and other Turkic republics of the Soviet Union. The importance of the role of I Turkological Congress was shown in Baku in 1926. Turkological Congress marked the transition of all the Turkic peoples, without exception, to the Latin alphabet. This step became a kind of premise in the reformation of the Turkish language, especially the graphics.